Perlawanan Kwee Kek Beng dalam rubrik Hindia and Holland dan Djamblang Kotjok pada surat kabar Sin Po 1923-1960 (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2021)
This article aims to describe the aspirations of the figure Kwee Kek Beng, an opinion maker in the history of the press movement in Indonesia from 1923-1960. The problem that will be studied in this article is: “How is Kwee Kek Beng’s effort in advancing the Sin Po newspaper, especially in Advancing the Sin Po Newspaper with Articles / Rubrics?” In the writing process, the writer uses historical methods in heuristics, source criticism, interpretation, and historiography with an interdisciplinary approach. Based on the research results, in developing the press movement in Indonesia, Kwee Kek Beng managed to become an opinion maker in Indonesia through his various controversial writings. Evidence of this is the exposure of Kwee Kek Beng to a press offense, the banning of the Sin Po newspaper. In his writings, Kwee Kek Beng conveyed various aspirations and concerns towards the government, especially in the years 1923-1960. This research showed the role of the mass media as the people’s voice and as means of resistance against colonialism.
Keywords: Chinese; Journalists; Journalism; Press; Sin Po